DEVELOPING HOTS QUESTIONS: EVALUATING PERSUASIVE SPEECH TEXT LEARNING IN GRADE IX OF JUNIOR HIGH SCHOOL (PENGEMBANGAN SOAL HOTS: EVALUASI PEMBELAJARAN TEKS PIDATO PERSUASIF DI KELAS IX SMP) - Riswanda Himawan; Pujiati Suyata (Universitas PGRI Sumatera Barat, 2022)
Indonesian language learning is learning that requires students' critical thinking processes. So that the teacher as a learning facilitator must be able to deliver students to achieve these indicators. However, in reality in the learning process in the classroom the teacher as a learning facilitator has not directed students into critical thinking through HOTS-oriented questions, especially in teaching persuasive speech texts. This happened because of the lack of teacher references to present HOTS-based questions. Based on the description, this research aims to; (1) describe the questions that have been used in teaching persuasive speech texts in class IX SMP, (2) describe the product design in the form of HOTS-based evaluation questions in teaching persuasive speech texts in class IX SMP, (3) describe the results of the product design validity test in the form of a question model (4) describing the results of a limited trial. In line with the title of this research, this research belongs to the type of Research and Development (R&D) Borg and Gall modified by Sugiyono. The method used in this research is descriptive qualitative and quantitative descriptive methods. Qualitative descriptive is used to describe the results of the needs analysis related to the questions developed. Quantitative descriptive is used to describe the correlation results related to the results of the validity test to experts calculated by the Aiken V formula. Based on the results of the study, it can be concluded that: (1) Teachers have not implemented and students have never worked on HOTS-oriented questions in persuasive speech text learning ( 2) The design model developed in this study was in the form of 27 questions. (3) the questions were then validated by 3 expert validators, the validation results were correlated with the Aiken V formula showing a score of 0.40-0.80 with a valid category (4) The results of the interviews related to limited trials conducted on 10 grade IX students were obtained The result is that students feel challenged by the questions being tested.